EFFICIENT VOICE-ACTIVATED ROBOTIC VEHICLE: ADVANCEMENTS IN AUTOMATION (International Journal of Food and Nutritional Sciences, 2021)
The goal of this project is to use voice commands sent via an Android application on a smartphone to operate a robotic car. Bluetooth technology facilitates the wireless communication link formed between the vehicle and the Android app. The primary goal of creating this voice-activated robotic car is to recognise human speech and respond to preprogrammed commands. The most fundamental commands in this list are stop, turn left, turn right, turn back, and forward. From an economics perspective, it is quite possible or economical to use Android smartphone technology to manage the vehicle remotely. The process is really straightforward. The Arduino Uno development board will be used to build the main processing unit, and a Bluetooth device interfaced with this processor will help digitalize commands received. Two DC motors will be used to build the moving mechanism, and a H Bridge IC-designed motor driving circuit will drive each of the two motors independently. The Bluetooth RF transmitter converts the commands received from the Android application through the phone microphone into digital signals, and its approximate range is 50 feet.